(untitled) (Jurnal Mekanikal, 2018)
There are several modes of transporting oil produced offshore to the processing site onshore. In doing so there are risks that oil spill might happen. In this paper offshore pipeline as a mode of transporting oil f rom an offshore Oilfield to the landfall site is being considered. The study also concerns the impact on the environment fromthe sources of damage to the subsea pipe line to the landfall site. Mitigative measures in the event ofoil spills are also discussed. In addition hazard that are associated with the operational phase of the project are also identified.